2018
DOI: 10.1002/jrs.5409
|View full text |Cite
|
Sign up to set email alerts
|

Initial excited‐state structural dynamics of uridine from resonance Raman spectroscopy

Abstract: The effect of the N1 ribose sugar on the initial excited‐state structural dynamics of uridine is explored with ultraviolet resonance Raman spectroscopy. Excited‐state slopes and broadening parameters were obtained by simulating the resonance Raman excitation profiles and absorption spectrum using a self‐consistent, time‐dependent formalism. The initial excited‐state structural dynamics of uridine look similar to those of uracil, in terms of the distribution of percentage of reorganization energy along differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Unfortunately, no vibrational assignments have been carried out for any of the homopentamers. However, the vibrational assignments and resonance Raman studies are reported for the nucleotide monomers. ,,,, Therefore, those reported vibrational mode assignments are used in further discussion. Though there were studies on the Raman signature of genomic DNA, those studies only show that the intensity and frequencies are sensitive to base sequences; they do not provide any insight into the excited-state structural dynamics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, no vibrational assignments have been carried out for any of the homopentamers. However, the vibrational assignments and resonance Raman studies are reported for the nucleotide monomers. ,,,, Therefore, those reported vibrational mode assignments are used in further discussion. Though there were studies on the Raman signature of genomic DNA, those studies only show that the intensity and frequencies are sensitive to base sequences; they do not provide any insight into the excited-state structural dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…There have been several resonance Raman studies on DNA and DNA components. Loppnow and co-workers have successfully used resonance Raman spectroscopy to understand the initial excited-state structural dynamics of the different nucleobases and their derivatives. , ,, , In thymine, the observed resonance Raman intensities suggest that C5C6 bond elongation is the primary structural dynamics. This bond elongation and the pyramidalization of C5 and C6, the other significant excited-state structural dynamics, are consistent with the thymine photochemistry. , In contrast, the C5H and C6H bending modes are the most intense modes in uracil, where the photohydrate is the major photoproduct .…”
Section: Introductionmentioning
confidence: 99%
“…Sasidharanpillai and co‐workers described the initial excited‐state structural dynamics of uridine from resonance Raman spectroscopy. The differences between thymine, thymidine, uracil, and uridine were examined, and the possible effect on the resulting differences in photochemistry were discussed …”
Section: Resonance Raman Spectroscopymentioning
confidence: 99%
“…The differences between thymine, thymidine, uracil, and uridine were examined, and the possible effect on the resulting differences in photochemistry were discussed. [128] 14 | ART AND ARCHAEOLOGY The use of Raman spectroscopy in art and achaeology provides an example of the growing application of Raman as a sensitive nondestructive technique that can be used both in the laboratory under controlled conditions but also in the field with compact portable instrumention that provides spectral measurements of matierials in situ without removal of samples to a laboratory setting. An area of growth is the use of micro-Raman spectroscopy that combines Raman scattering with optical microscopy so that one can obtain Raman spectra from microscopicsized specimens as well as their corresponding optical images.…”
Section: Time-resolved and Ultrafast Raman Spectroscopymentioning
confidence: 99%
“…Moreover, the study of the excited state dynamics of DNA and its constituents has attracted a lot of interest in recent decades [36][37][38][39], due to the biological and medical relevance of the photochemical processes triggered in DNA by UV absorption, which can lead to the damage of the genetic code [36]. Consequently, vRR has been widely adopted to investigate the structural dynamics of photoexcited nucleobases [35,[40][41][42][43][44][45], nucleotides, [46], and oligonucleotides, [47,48], to cite some relevant papers. More recently, vRR has been used to characterize more complex DNA structures, and their interactions with therapeutic ligands [49][50][51][52][53].…”
Section: Introductionmentioning
confidence: 99%